The Efficiency of Dynamic Electricity Prices - Andrew J. Hinchberger; Mark R. Jacobsen; Christopher R. Knittel; James M. Sallee; Arthur A. van Benthem (CESifo GmbH, 2024)
The marginal cost of electricity fluctuates hour-by-hour, yet retail customers typically face flat prices. Using data from all seven US wholesale markets and a new method to evaluate alternative rates set in advance that accounts for equilibrium price effects, we estimate efficiency gains from time-varying price schedules that better align price with cost. We have three main results. First, time-of-use rates and critical-peak pricing, the two most common time-varying rate plans, each correct about 10% of mispricing. Second, complex rate structures based on historical prices often backfire. Third, real-time pricing with price ceilings can capture most potential efficiency gains.
Keywords: L94; L97; Q41; Q48; 330; electricity; time-of-use pricing; critical- peak pricing; real-time pricing; efficiency